Musical Form and Musical Performance - Cone, Edward T. (London Norton, 1968)
The first three chapters of Musical Form and Musical Performance are revised and expanded versions of lectures given at Oberlin College Conservatory of Music in 1968, with an addition of a fourth chapter on esthetic perception (which does not deal directly with the topic of rhythm and meter). The questions that Cone brings forth throughout these essay s are those that he hopes will "throw some light on a problem... : how to achieve valid and effective musical performance." (p.12) Knowing the form of a piece is what will enable a performer to achieve the goal of an effective performance. Cone conceives musical form as being basically rhythmic. In Chapte r 1, "The Picture and the Frame: The nature of Musical Form," Cone compares musical works with paintings in an art gallery. A painting has a frame marking the limits of the picture, as well as separating it from the 'real' world around it. Cone believe s that a musical work also contains a frame - silence or actual music which in effect separates the composition from the world around it. He also makes a careful distinction between a frame and an introduction, which is defined as an expanded upbeat lead ing to the structural downbeat. Also in this chapter Cone discusses the idea that the cadence is the goal of musical motion. He therefore believes that the conventional strong/weak alternation of beats cannot apply to rhythmic analysis. Rather, Cone de scribes different types of strong points in a musical phrase, including the initial accent and the cadential accent, with many varying degrees of medial strong points in between. In Chapter 2, "Inside the Picture: Problems of Performance," Cone further illustrates that any effective performance depends upon the communication of the rhythmic life of a composition. Cone demonstrates that the principles at work on higher levels than phrases and periods can only be made clear in performance if the performe keeps in mind that the whole is greater than any of its parts. Cone also discusses the matter of the conventional literal repetition, and whether or not they should be included in performance. He includes many justifications for adhering to the repeats , the most general being that of throwing new light on old material. Cone also brings up the issues of relating the cadences to the themes in different ways: the dominant cadence to the theme in tonic, the cadence continued in the same key in the develo pment, and the cadence in tonic followed by the theme in the dominant. He also warns performers that all interpretive decisions must have a clear purpose in mind. In the third chapter, "The Picture Gallery: From and Style," Cone characterizes the Baroq ue and Classical styles by their respective rhythmic features: Baroque by the uniformity of the beat as the basic metric pulse and Classical by the measure as the basic metric pulse, citing examples from Bach and Mozart, among others. Cone also mentions that the Romantic era can be similarly categorized, with the hyper-measure as the basic metric pulse.
Keywords: Musical analysis; Performance